2010
DOI: 10.1038/sj.bjc.6605726
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of the safety and pharmacokinetics of the histone deacetylase inhibitor belinostat administered in combination with carboplatin and/or paclitaxel in patients with solid tumours

Abstract: Background:This phase I study assessed the maximum tolerated dose, dose-limiting toxicity (DLT) and pharmacokinetics of belinostat with carboplatin and paclitaxel and the anti-tumour activity of the combination in solid tumours.Methods:Cohorts of three to six patients were treated with escalating doses of belinostat administered intravenously once daily, days 1–5 q21 days; on day 3, carboplatin (area under the curve (AUC) 5) and/or paclitaxel (175 mg m−2) were administered 2–3 h after the end of the belinostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 20 publications
5
44
0
Order By: Relevance
“…67 A Phase I study of solid tumors showed that the belinostat/ paclitaxel combination is tolerable in humans and thus feasible for further clinical study. 71 Recently approved nanoparticle formulations of vincristine and paclitaxel that increase efficacy and reduce toxicity 72,73 should make them safer to combine with other drugs such as belinostat. Using a preclinical model of aggressive DLBCL the current study has demonstrated the potential of combining MTAs with belinostat for treatment of relapsed/refractory DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…67 A Phase I study of solid tumors showed that the belinostat/ paclitaxel combination is tolerable in humans and thus feasible for further clinical study. 71 Recently approved nanoparticle formulations of vincristine and paclitaxel that increase efficacy and reduce toxicity 72,73 should make them safer to combine with other drugs such as belinostat. Using a preclinical model of aggressive DLBCL the current study has demonstrated the potential of combining MTAs with belinostat for treatment of relapsed/refractory DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, combinations with other agents are required to optimise their efficacy [12]. HDACi have shown synergistic or additive antitumor effects with conventional anticancer drugs, targeted agents and radiation [7,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The steady state volume of distribution is 22.6 ± 9.7 L/m 2 with a clearance of 41.1 ± 22.2 L/h/m 2 . 4 In another report following a 30-minute infusion of 1,000 mg/m 2 , the peak concentration (C max ) is 32,124 ± 9,128 ng/mL. The AUC is 9,990 ± 3,420 ng•h/mL.…”
Section: Pharmacokineticsmentioning
confidence: 96%